Effect of proximity to Manila Light Rail Transit System Line 2 on the price of commercial lands - Go, Sabrina Joyce U. (School of Economics, University of the Philippines Diliman, 2019)
As the scene and the city horizon in Metro Manila changed so radically in the past few decades, partially attributable to the boom and bust cycles of land prices, it would be interesting to determine whether proximity to stations of the rail systems play a role in the prices of commercial land. We chose to focus on commercial land over residential land due to data constraints. We control for the following variables that could have an impact on land prices _ infrastructure proxied by hospital, school, supermarket or mall, flood zone, population, and when the street contains a condominium building. We test for the location and accessibility theory of commercial lands in the urban area using the land prices obtained from the BIR, and distances calculated using the great circle distance formula. The two main models used in our study is the Ordinary Least Squares regression model (OLS) to determine the effect of distances of the LRT_2 stations on land prices, and the Difference in Difference regression model (DID) to show a comparison between the effect of distance on land values before and after the construction of LRT_2. The main limitation of our study is the lack of data to create a more comprehensive dataset. We suggest obtaining more observations in the future to further strengthen our results. Our findings suggest that the closer the street within a station_s 2 km radius was to its respective station, the higher the price placed on its land, the close proximity makes it more convenient for the public to access them, thus increasing the demand for the land in those areas, which subsequently leads to an increase in price.